2013
DOI: 10.1371/journal.pone.0072464
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthetic Monoketone Transmute Radiation-Triggered NFκB-Dependent TNFα Cross-Signaling Feedback Maintained NFκB and Favors Neuroblastoma Regression

Abstract: Recently, we demonstrated that radiation (IR) instigates the occurrence of a NFκB-TNFα feedback cycle which sustains persistent NFκB activation in neuroblastoma (NB) cells and favors survival advantage and clonal expansion. Further, we reported that curcumin targets IR-induced survival signaling and NFκB dependent hTERT mediated clonal expansion in human NB cells. Herein, we investigated the efficacy of a novel synthetic monoketone, EF24, a curcumin analog in inhibiting persistent NFκB activation by disrupting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…The subcutaneous administration of human SH-SY5Y cells resulted in the development of ~200 mm 3 xenografts in ~70 % of the animals within 30 days, as described previously [ 26 , 31 ], while the other 30 % of the mice were presented with multiple clinically-mimicking aggressive metastatic tumors in the mediastinum and retroperitoneal, pelvic, abdominal, and chest cavities as shown previously (27).
Fig.
…”
Section: Resultssupporting
confidence: 63%
“…The subcutaneous administration of human SH-SY5Y cells resulted in the development of ~200 mm 3 xenografts in ~70 % of the animals within 30 days, as described previously [ 26 , 31 ], while the other 30 % of the mice were presented with multiple clinically-mimicking aggressive metastatic tumors in the mediastinum and retroperitoneal, pelvic, abdominal, and chest cavities as shown previously (27).
Fig.
…”
Section: Resultssupporting
confidence: 63%
“…Xenotransplantation of SH-SY5Y cells resulted in the development of ~200 mm 3 xenografts in ~70 % of the animals within 30 days (Fig. 1a ) [ 53 , 54 ]. About 30 % of the mice that received identical clones initially (within 10–20 days) showed xenograft development, then subsided to a residual tumor (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EF24 robustly conferred radiation-induced cell death mainly by inhibiting radiation-induced NF-κB signaling in breast cancer (43). In the same year, the same group found that EF24 can suppress the radiation-induced NF-κB-DNA binding activity/promoter activation in genetically varied human neuroblastoma (44). Inhibition of the NF-κB signaling extends the therapeutic application of EF24 to other NF-κB-dependent diseases, such as inflammatory diseases (described below).…”
Section: Biological Activities and Mechanisms Of Action Of Ef24mentioning
confidence: 97%